The language of agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
English resource book for agriculture Elias Modern Publishing House, Egypt and Macmillan Education Publishers, UK, 2001. 320 pp. ISBN 0333 96773 9